The Semiotics of Cultural Commodification: Repackaging The English Afternoon Tea Tradition For Modern Tourism - Maryam, Evin; Budiwaty, Suci (ITScience (Information Technology and Science), 2025)
In the digital era, cultural traditions are often reinterpreted and commodified through modern marketing platforms. The English Afternoon Tea tradition, once associated with aristocratic leisure and social refinement, has been transformed into a lifestyle attraction promoted through tourism and culinary branding. This study investigates how the commodification of the English Afternoon Tea tradition is represented semiotically in Brigit’s Bakery’s Instagram content. It aims to reveal how the brand redefines traditional English cultural values to appeal to modern audiences and global tourism markets. Employing Charles Sanders Peirce’s semiotic framework, this qualitative research analyzes selected visual and textual materials from Brigit’s Bakery’s official Instagram account. The analysis focuses on the triadic relations of signs—icon, index, and symbol—to uncover how cultural meanings of Afternoon Tea are transformed into attractive and marketable representations. The findings show that Brigit’s Bakery recontextualizes Afternoon Tea through visual nostalgia, elegant minimalism, and symbolic reinterpretation. The process transforms a cultural ritual of tradition and intimacy into a consumable experience emphasizing aesthetics, modern comfort, and tourism appeal. The commodification of Afternoon Tea in Brigit’s Bakery’s digital marketing illustrates a negotiation between authenticity and consumerism. Through semiotic transformation, English classical culture is preserved in form but adapted in meaning to suit modern lifestyle and tourism narratives.